The future of the self : understanding personalization in childhood and beyond - Kucirkova, Natalia (Emerald Publishing Limited, 2021)
In a time of automated personalized ads, artificially intelligent social robots, and smart devices in the homes of millions, it has become critically important to understand the impact of our digitized selves - especially upon our younger generations. When children as young as three can take their own selfies, and customise their own avatars, how should we respond to the opportunity and threat of digital personalization for young children? Tracing thematic links between trends that are often addressed separately, and drawing on multidisciplinary research evidence, Kucirkova offers a comprehensive account of the effects of digitally-mediated personalization on children's development of 'self'. Looking to the future, she provides a balanced account of the positives and negatives of personalisation against the backdrop of broader societal trends, such as globalisation/localisation, (de)centralisation of services and communication. Providing critical thinking tools, Kucirkova challenges us to understand the profound implications that the personal data economy and network-based technologies might have played in our own understanding of ourselves and each other.